KINERJA KEUANGAN DALAM SOROTAN: APA YANG MEMPENGARUHINYA? - marhamah, Marhamah; Widyartati, Penta (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
Return on Asset (ROA) is a ratio used to measure profitability. It is a financial ratio that assesses how efficiently a company utilizes its total assets to generate profit. The research findings indicate that current ratio and debt to asset ratio have a significant effect on return on asset, whereas debt to equity ratio does not affect return on asset.